Potential role of serum homocysteine and uric acid level as a predictive marker for pre-eclampsia - Kunwar, Saroj; Thakur, Rajesh Kumar; Nepal, Rupa; Paudel, Lakshan; Chaulaigai, Bimal; Paudel, Govinda Akela (International Journal of Scientific Reports, 2019)
Background: Hypertension is one of the common disorders during pregnancy and can cause severe health complications for both mother and developing fetus. Pre-eclampsia (PE) is a form of hypertensive disorder complicating pregnancy. This study was aimed to estimate serum uric acid and homocysteine level as a potential biomarker for prediction of preeclampsia. Methods: 85 pre-eclamptic pregnant women and 50 normotensive pregnant women were recruited from department of Obstetrics and Gynecology, Star Hospital after obtaining the informed written consent. Blood samples were collected and analyzed for serum homocysteine and serum uric acid level. Results: Serum uric acid and homocysteine levels were found to be significantly higher in pre-eclamptic cases than in controls (6.5±0.7 mg/dl and 13.5±5.4 µmol/l in cases versus 4.3±0.8 mg/dl and 10.1±4.6 µmol/l in healthy controls). Maximum sensitivity and specificity of serum uric acid was obtained at a cut-off of 5.5 mg/dl (sensitivity- 91% and Specificity- 88%) and serum homocysteine at 10.7 µmol/l (sensitivity-67% and specificity-64%) respectively. Conclusions: At optimum cut off value serum uric acid showed highest sensitivity and specificity for diagnosis of pre-eclampsia. Thus, serum uric acid level is better predictive marker compared to serum homocysteine level for pre-eclampsia.